Pomen intravenskih imunoglobulinov pri zdravljenju krvnih bolezni odraslih - Glaser, Marjana (Zdravniški vestnik, 2008)
Intravenous immunoglobulins (IVIG) are preparations made from human plasma and contain beside immunoglobulin G a wide spectrum of other endemic antibodies against infectious disease typical for Slovenia. The purpose of treatment with IVIG is to restore normal immunoregulatory mechanisms in human body. The use of IVIG is different: as replacement therapy in primary and secondary immunodidefficiency (lack of antibodies, impossibility of producing antibodies), as prophylactic treatment of some infections (cytomegalovirus, parvovirus B19) and for treatment of autoimmune diseases as idiopathic thrombocytopenic purpura. Conclusions. As showed with pharmacokinetics study in patients with chronic lymphocytic leukemia and multiple myeloma, IVIG has no influence on normal distribution of IgG and other antibodies. In the paper there are shown multiple possible mechanisms of IVIG action, although they haven't been understood yet. There is a big possibility that some other antibodies, which are present in the IVIG, are involved. The relative good effect of IVIG treatment in different hematological diseases became of interest for prevention and treatment of some neurologic and neuromuscular diseases.
Keywords: Agamaglobulinemija; Agammaglobulinemia; Immunoglobulins, Intravenous; Imunoglobulini, intravenski; imunologija; intravenski imunoglobulini; krvne bolezni; Limfoproliferativne motnje; Lymphoproliferative Disorders; Multiple Myeloma; Multipli mielom; pripravki; Purpura, Thrombocytopenic, Idiopathic; Purpura, trombocitopenična, idiopatska; therapy; zdravljenje